Detection of Snps in the Melanocortin 1-Receptor (MC1R) and Its Association with Shank Color Trait in Hs Chicken - Shen,X (2019)
ABSTRACT The melanocortin 1 receptor (MC1R) gene plays a key role in controlling the deposition of melanin. In mammals, the MC1Rgene is regarded as a major candidate gene in the control of melanin formation. In domestic animals, the MC1R gene mainly controls the expression of coat, skin, and plumage color in mammals and birds. In order to breed chickens with dark-green shank faster, we screened the molecular markers for shank color in a HS chicken population by exploring the relationship between polymorphism of the MC1R gene and three different shank colors (light green, dark green and yellow). Two primer pairs for code region of the MC1R gene were designed in the basic of chicken genomic sequence. DNA sequencing was performed to detect the polymorphisms and PCR was used to amplify DNA fragment. Sequences analysis indicated that 7 SNPs were predominant the three HS chicken populations with different shank color, including g.18,287,945C>T, g.18,288,088T>C, g.18,288,150G>A, g.18,288,303A>G, g.18,288,512G>A, g.18,288,513T>C, and g.18,288,520A>C. Association analysis revealed that the dark-green shank population showed moderate polymorphism, whereas the light-green shank population showed low polymorphism among overall 7 SNPs and that SNP6 (g.18,288,513T>C) may be significantly associated with three different shank colors in HS chickens. The haplotype CTGGACA had the largest haplotype frequencies, accounting for 56.22%, and the haplotype combination H1H1 is mainly distributed in the dark-green shank population, and may be used as molecular maker for marker-assisted selection of shank color in HS chickens.